Personal autonomy through education - Beaver, Anthony R. (1987)
The concept of personal autonomy as an educational ideal is analysed from its etymological roots of autos and nomos. The autos is shown to be most closely associated with authenticity and this concept is explored from existentialist roots. Authenticity's points of contact with reason are examined and the authentic individual is shown to be a deep, reflective evaluator of his own motives but existentialist radical choice of self is shown to be essentially incoherent. The nomos is linked to reason and the criteria it picks out. The limits upon reason are considered but its significance to personal autonomy is shown to be considerable; reason is argued to embrace feeling and a dimension of practical reason. The adjective, personal, is not redundant within personal autonomy as an educational ideal and is held to have significant moral implications for autonomy. A Millian analysis of the 'endowment' of a person is considered and perspectives from both developmental psychology and an ancient tradition embracing persons and virtues are shown to relate to autonomy. The second part of the thesis considers the relationship of personal autonomy to three related concepts in education: authority, freedom and paternalism and points of contact are clarified. The final part examines a place for personal autonomy within educational activities in schools. It is argued that personal autonomy should be exercised in school- based education as its exercise is the only sure way to develop it. Therefore a perspective of education as a series of practices in which the learner should be enabled to engage exercising a measure of personal autonomy is the theme of the final part. However, the purpose of the thesis is a clarification of fundamentals; it does not purport to present a curriculum for personal autonomy.